ChemInform Abstract: Enantioselective Organocatalytic One‐Pot Amination/Aza‐Michael/Aldol Condensation Reaction Sequence: Synthesis of 3‐Pyrrolines with a Quaternary Stereocenter. Issue 10 (7th March 2013) - Desmarchelier, Alaric; Coeffard, Vincent; Moreau, Xavier; Greck, Christine
Abstract The described reaction sequence is an efficient and highly enantioselective synthesis of the title compounds (IV), which can be used for further transformations.